On the Onset of Thermal Instability of a Porous Medium Layer Saturating a Jeffrey Nanofluid - RANA, G. C.; GAUTAM, Poonam Kumari (Engineering Transactions, 2022)
The onset of stationary convection in thermal instability of porous layer saturating a Jeffrey nanofluid is studied. The behaviour of nanofluid is described by a Jeffrey fluid model and the porous layer is assumed to follow Darcy’s law. Due to the presence of the Jeffrey parameter and nanoparticles, the momentum-balance equation of fluid is modified. The linear stability analysis and normal modes analysis method are utilised to derive the dispersion relation for the Rayleigh number in terms of various parameters for free-free boundaries. The effects of the Jeffrey parameter, Lewis number, modified diffusivity ratio, nanoparticles’ Rayleigh number and medium porosity on the physical system are discussed analytically and graphically.